2008
DOI: 10.1103/physrevb.77.064417
|View full text |Cite
|
Sign up to set email alerts
|

Role of conduction electrons in mediating exchange interactions in Mn-based Heusler alloys

Abstract: Because of the large spatial separation of the Mn atoms in Heusler alloys ͑d Mn-Mn Ͼ 4 Å͒, the Mn 3d states belonging to different atoms do not overlap considerably. Therefore, an indirect exchange interaction between Mn atoms should play a crucial role in the ferromagnetism of the systems. To study the nature of the ferromagnetism of various Mn-based semi-and full-Heusler alloys, we perform a systematic first-principles calculation of the exchange interactions in these materials. The calculation of the exchan… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

11
116
0
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 205 publications
(129 citation statements)
references
References 157 publications
11
116
0
2
Order By: Relevance
“…34 Previously in literature 20 it was mentioned for A 2 MnC systems (A=Cu, Pd; C=Al, In, Sb), that the conduction electrons of the C atom take role in the coupling between Mn atoms. But in a recent study 22 the role of conduction electron of A atom has also been confirmed for a number of Mn-based Heusler alloys. In our studied systems here, for a given series of materials, C-atom is fixed which is Ga for Ni 2−x Co x MnGa, Ni 2−x Co x FeGa, Pt 2−x Co x MnGa and Sn for Pt 2−x Co x MnSn.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…34 Previously in literature 20 it was mentioned for A 2 MnC systems (A=Cu, Pd; C=Al, In, Sb), that the conduction electrons of the C atom take role in the coupling between Mn atoms. But in a recent study 22 the role of conduction electron of A atom has also been confirmed for a number of Mn-based Heusler alloys. In our studied systems here, for a given series of materials, C-atom is fixed which is Ga for Ni 2−x Co x MnGa, Ni 2−x Co x FeGa, Pt 2−x Co x MnGa and Sn for Pt 2−x Co x MnSn.…”
Section: Resultsmentioning
confidence: 99%
“…20 Additionally, there is also an indirect RKKYtype exchange mechanism 21 between the B atoms, primarily mediated by the electrons of the C atoms, which also plays an important role in defining the magnetic properties of these materials. 20,22 Staunton et al 23 reported the role of RKKY interaction behind the origin of magnetic anisotropy of a system. For the magnetic shape memory alloys, magnetic anisotropy energy plays an important role.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the interplay between the localized d electrons and the delocalized electrons in Mn based Heusler systems is still under discussion, and in this context the shape of the Fermi surface is a key ingredient of the Ruderman-KittelKasuya-Yosida (RKKY) interaction [7,[11][12][13]. Besides these fundamental questions, Cu 2 MnAl has also a large relevance for applied physics as a neutron polarizer and monochromator material [14,15].…”
mentioning
confidence: 99%
“…Being the prototype of all Heusler alloys [8], Cu 2 MnAl has also become a model system for understanding the electronic correlations in this class of materials [2,7,9,10]. In particular, the interplay between the localized d electrons and the delocalized electrons in Mn based Heusler systems is still under discussion, and in this context the shape of the Fermi surface is a key ingredient of the Ruderman-KittelKasuya-Yosida (RKKY) interaction [7,[11][12][13].…”
mentioning
confidence: 99%
See 1 more Smart Citation